Alkylglycerol: not abundant but promising functional lipid - Wang, Hai-Long; Tan, Chin Ping; Liu, Yuanfa; Xu, Yong-Jiang (Elsevier, 2024)
Background: Alkylglycerols are a special class of functional ether lipids. In recent years, these functional lipids have garnered significant attention due to their unique biological functions, such as anti-obesity, anti-cancer, anti-inflammatory, and anti-cardiovascular disease properties. Scope and approach: This article summarizes the natural sources, analytical methods, digestion and absorption properties, endogenous occurrence, and nutritional effects of alkylglycerols. It intends to provide a compre hensive and up-to-date review of the distribution and function of alkylglycerols and the problems encountered in current research. Key findings and conclusions: Marine organisms, especially cartilaginous fish, are the main source of alkylgly cerols, whereas terricolous plants remain to be further investigated for the presence of alkylglycerols. Mean while, microorganisms are a novel and valuable source of alkylglycerols. Besides, processing and storage treatments can also affect the molecular species of esterified alkylglycerols and plasmalogens in various foods, especially milk. GC-MS and LC-MS are the commonly used methods for the analysis of alkylglycerols in food and biological samples. Notably, the bioavailability of dietary alkylglycerols exhibits a negative correlation with the expression levels of alkylglycerol monooxygenase in intestinal epithelial cells. Dietary intake of alkylglycerols could greatly enrich endogenous ether lipid levels in various peripheral tissues (such as those of plasmalogens), which in turn could contribute to the prevention of various diseases. However, the causal relationship between decreased or increased levels of endogenous ether lipids and the development of various diseases remains un clear. In conclusion, alkylglycerols are a promising class of functional lipids, but further studies are required to elucidate the existing problems.